PARTISIPASI POLITIK PEREMPUAN INDONESIA DALAM RELASI GENDER - Suryadi Suryadi (ORASI: Jurnal Dakwah dan Komunikasi, 2015)
From quantitative measurement, gender discrimination is still a reality in our country. Woman is less access in development than man.  Government seemingly is not serious in implementing gender mean streaming in development, whereas Indonesia has been consensus to support and implement international conventions and agreements in gender empowerment. This situation has to be changed by more increase woman quality. One principal aspect to do that is by strengthening woman bargaining position in politic. Meanwhile, 30 percent quota of woman in parliament is still not be implemented. Many parties are still uncertain in woman capabilities cause of gender paradigm that is unbalanced. Recently, gender discrimination is still operating in work place, in community and in any segment of our life. Thus, government has to be more serious in supporting gender empowerment, especially in bureaucracy. Parliament also has to initiate in creating regulation which pro woman. NGOs, university, gender study center also have to be more concern in women in diverse background; rural, city, career woman, etc.Key words: Gender discrimination, political position of woman